مشكلات التعليم المفتوح من وجهة نظر طلبة التعليم المفتوح في جامعة دمشق - الجشي سيناء الخطيب; ذياب رشا نعيم (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدفت الدراسة إلى تعرف أهم مشكلات التعليم المفتوح من وجهة نظر طلبة التعليم المفتوح في جامعة دمشق. طبق البحث على الطلاب والطالبات المسجلين في السنة الأخيرة في التعليم المفتوح للعام الدراسي2012/ 2013م . يتكون المجتمع الأصلي للدراسة من 2100 طالب، أمّا عينة الدراسة فقد شملت(210( طالباً وطالبةً بنسبة 10% من المجتمع الأصلي، وتم اختيارهم بصورة عشوائية. واتبعت الباحثة المنهج الوصفي التحليلي في البحث واستخدمت الاستبانة كأداة لتحقيق أهداف البحث بعد التحقق من صدقها وثباتها موجهة لطلبة التعليم المفتوح في جامعة دمشق تضمنت أربعة أبعاد:(الشؤون الإدارية (16بنداً)، المقررات (10بنود)، الامتحانات(4بنود)، الأساتذة (5 بنود)). وأشارت النتائج إلى ما يأتي: إنّ مشكلات التعليم المفتوح تقع في مستوى المشكلات المتوسطة وهذا الأمر يشير إلى أن طلبة التعليم المفتوح في جامعة دمشق يشعرون بهذه المشكلات. عدم وجود فروق دالة إحصائياً في متوسط درجات أفراد عينة الدراسة على استبانة مشكلات التعليم المفتوح تعزى إلى متغير الجنس. عدم وجود فروق دالة إحصائياً في متوسط درجات أفراد عينة الدراسة على استبانة مشكلات التعليم المفتوح تعزى إلى متغير التفرغ الدراسي. عدم وجود فروق دالة إحصائياً في متوسط درجات أفراد عينة الدراسة على استبانة مشكلات التعليم المفتوح تعزى إلى متغير التخصص. وانطلاقاً من النتائج الميدانية التي توصلت إليها الباحثة، فهي تقدم المقترحات التالية: · تدريب الأساتذة على تقنيات التعليم المفتوح وعلى كيفية توظيفها في المناهج الدراسية. · البحث عن مقر آخر لمركز التعليم المفتوح وتصميمه بما يناسب متطلبات هذا التعليم. This research has aimed to identify the most important problems in the Open Learning from the students’ viewpoint in the University of Damascus. The survey has been applied on the enrolled students of the Final Year of the Open Learning in 2012- 2013 . The original population of the study is (2100) students. As for the study sample, it included (210) students from the original population which might constitute 10% of the original population, they have been chosen randomly. The researcher has followed the descriptive analytical approach in her survey and she has used the questionnaire as a means to achieve the objectives of the research for the students at the University of Damascus, Open Learning, after it was tested for its validity and reliability. It included four dimensions:(the administrative affairs (16 items), curricula (10 items), examinations (4 items), teachers ( 5 items)). The results indicated the following: The problems of the Open Learning are in the medium problems level. This indicates that the students of the Open Learning at the University of Damascus observethese problems. There were no satistical differences in the mean scores of individuals of the sample towards the problems of the OpenLearning related to the gender variable. There were no satistical differences in the mean scores of individuals of the sample towards the problems of the OpenLearning related to the full–time academic variable. There were no satistical differences in the mean scoresof individuals of the sample towards the problems of the OpenLearning related to the speciality variable. The researcher presents the following suggestions,after presenting the field results that she has come it: Training teachers on the Open Learning techniques and how to employ them in the curricula. Finding another location for Open Learning center and deciding it to suit the requirements of the Open Learning.